The history of the African collection of the City Museum in Bydgoszcz - Frischke , Gabriela (Acta Archaeologica Lodziensia, 2023)
The article was created as part of research on wartime losses of the Leon Wyczółkowski District Museum in Bydgoszcz. It describes the history of the African collection belonging to the Historical Society of the Noteć Oblast, which from 1923 belonged to the City Museum. In 1944, the collection, along with other collections of the Museum, was taken to Dębowo for protection. According to people involved in the return of the objects to Bydgoszcz, the manor house was burned down and the exhibits hidden there were destroyed. The collection was considered a wartime loss. However, it turned out that this was false information, and the collection was transferred in 1950 to the Folk Cultures Museum in Warsaw. The text analyzes documents describing the history of the collection, compares preserved inventories and lists, and attempts to trace the post-war fate of the collection.